된장분말을 첨가한 국수의 품질 특성 - 박복희; 고경미; 차민혜; 김솔; 전은례; Bock-Hee Park; Kyeong-Mi Koh; Min-hye Cha; Sol Kim; Eun-Raye Jeon (Journal of the Korean Society of Food Culture, 2016)
This study evaluated the quality characteristics of dried noodles prepared with doenjang powder (0, 3, 6, 9%) in order to determine the most preferred noodle recipe. The proximate composition of the composite doenjang powder-wheat flours was as follows: calories 365 kcal, carbohydrates 79 g, saccharides 3 g, protein 10 g, fat 0.8 g, and sodium 65 mg. As the level of doenjang powder increased, the content of total amino acids increased; aspartic acid, glutamic acid, tyrosine, and lysine contents increased, in particular. Water-binding capacity decreased as the level of doenjang powder increased. When viscosity of composite doenjang powder-wheat flours was measured by amylography, gelatinization point increased as the level of doenjang powder increased. As the level of doenjang powder increased, L value decreased, whereas a and b values increased. Weight, water absorption, and volume of cooked noodles decreased, whereas turbidity of soup increased. For textural properties, hardness decreased, whereas springiness increased as the level of doenjang powder increased. For overall preference according to the results of sensory evaluation, noodles added with 3% doenjang powder were the most preferred. According to the results, addition of doenjang powder positively affects the overall sensory evaluation of dried noodle, and 3% is the optimal level for addition.